Tensile strength of flax fabrics to be used as reinforcement in cement-based composites: experimental tests under different environmental exposures. (1st July 2019) - Ferrara, Giuseppe; Coppola, Bartolomeo; Di Maio, Luciano; Incarnato, Loredana; Martinelli, Enzo
Abstract: The use of Textile-Reinforced-Matrix (TRM) systems is gaining consensus as a possible technical solution for strengthening masonry structures. In this context, the use of natural fabrics (among which those made of flax) instead of synthetic ones can have a positive impact on several sustainability-related aspects, such as renewability, recyclability, biodegradability, low price. However, both mechanical properties and durability performance of natural fibres and fabrics needs to be further investigated with the aim to make it possible their use in composites for construction. Furthermore, this paper reports the results of a fundamental study on a bidirectional flax fabric eventually intended as the reinforcement in cement-based composite systems. Specifically, it aims at determining the tensile strength of flax of fibres, threads and the fabrics, and investigating how they are influenced by various environmental exposures and aging processes. The results in the experimental tests reported herein show that fibres and fabrics suffered no significant reduction in tensile strength due to the considered environmental exposure. Despite the common belief that natural fibres may be affected by durability issues, the results demonstrate that the flax fabric under investigation can be utilised as a reinforcement in TRM systems, which is the main novelty and original contribution of this paper.